어머니 문지기행동 척도 개발 및 타당화 연구 - 이영환(Young Hwan Yee); 한지현(Jihyeon Han) (Korean Journal of child studies, 2018)
Objectives: The purpose of this study was to develop and validate a scale of maternal gatekeeping based on the conceptual model by Puhlman and Pasley (2013). We alslo aimed to classify eight types based on three dimensionss (=control, encouragement, and discouragement) of maternal gatekeeping and characterized each type. Methods: Subjects were 200 mothers with their first child under three years of age. The Korean Maternal Gatekeeping Scale (KMG) was modified and developed according to the current situation in Korea based on previous research on this scale (Fagan & Barnet, 2003; Puhlman, 2013; Van Egeren & Hawkins, 2004). The analyses assessed content validity, reliability, factorial validity, construct validity, and criterion validity. Results: First, we developed and tested a new measure to assess the three dimensions of maternal gatekeeping as outlined by Puhlman and Pasley (2013), determining that the scale showed valid and reliable measures. Second, we classified eight types based on the three dimensions of maternal gatekeeping behavior: type 1 (high control, low encouragement, high discouragement) was the most frequent, while type 7 (low control, high encouragement, high discouragement) was the least frequent. Third, according to the types of maternal gatekeeping, there were differences in coparenting and parenting stress. Type 3 and 4 showed high co-parenting solidarity, co-parenting support, and shared parenting, type 5 and 7 presented high parenting stress. Conclusion: This study was significant in that it developed a Korean mothers' gatekeeping behavior scale based on three dimensions, classifying eight types of maternal gatekeeping behaviors. KCI Citation Count: 3